2010
DOI: 10.1111/j.1463-1318.2010.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for successful sacral nerve stimulation in the treatment of faecal incontinence: results of trial stimulation in 200 patients

Abstract: Stool consistency and low stimulation intensity have been identified as predictive factors for the short-term outcome of SNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 28 publications
2
41
1
5
Order By: Relevance
“…Dynamic graciloplasty is nowadays very rarely proposed in the treatment of fecal incontinence because the technique is complex, expensive and has a high morbidity rate [3]. Despite a certain level of expertise, our results with the artificial bowel sphincter, like other authors have recently shown, are less promising than those previously published in the literature [4].Sacral nerve modulation, first developed for the treatment of urinary dysfunction, is another option that has proved to be effective in the treatment of fecal incontinence in patients with an intact or nearly intact sphincter complex [5]. Some authors have demonstrated that sacral neuromodulation could also be beneficial in patients with sphincter defects, in patients presenting with fecal incontinence following anterior resection and chemoradiation for rectal cancer, and in patients suffering from systemic sclerosis or Crohn's disease.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Dynamic graciloplasty is nowadays very rarely proposed in the treatment of fecal incontinence because the technique is complex, expensive and has a high morbidity rate [3]. Despite a certain level of expertise, our results with the artificial bowel sphincter, like other authors have recently shown, are less promising than those previously published in the literature [4].Sacral nerve modulation, first developed for the treatment of urinary dysfunction, is another option that has proved to be effective in the treatment of fecal incontinence in patients with an intact or nearly intact sphincter complex [5]. Some authors have demonstrated that sacral neuromodulation could also be beneficial in patients with sphincter defects, in patients presenting with fecal incontinence following anterior resection and chemoradiation for rectal cancer, and in patients suffering from systemic sclerosis or Crohn's disease.…”
mentioning
confidence: 82%
“…Sacral nerve modulation, first developed for the treatment of urinary dysfunction, is another option that has proved to be effective in the treatment of fecal incontinence in patients with an intact or nearly intact sphincter complex [5]. Some authors have demonstrated that sacral neuromodulation could also be beneficial in patients with sphincter defects, in patients presenting with fecal incontinence following anterior resection and chemoradiation for rectal cancer, and in patients suffering from systemic sclerosis or Crohn's disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be mentioned that the therapeutic outcome of SNS is diminished in patients with chronic diarrhea. Only one publication indicates a better therapeutic effect in patients with loose stool consistency [23].…”
Section: Item 32mentioning
confidence: 99%
“…Rasmussen et al 17 , reportan una tasa de infección del 5%. En el multicéntrico francés 24 , la tasa descrita, es muy inferior, 1,5%, misma cifra comunicada por Michelsen et al 21 . Tjandra et al 25 , no presentaron ninguna infección, sobre 60 pacientes.…”
Section: Fase De Implantación Del Generador Definitivounclassified